Pengaruh Massage Effleurage Terhadap Pengurangan Tingkat Nyeripersalinan Kala I Fase Aktif pada Primigravida di Ruang Bougenville Rsud Tugurejo Semarang - Priharyanti Wulandari; Prasita Dwi Nur Hiba (Jurnal Keperawatan Maternitas, 2015)
On preliminary studies conducted in local General Hospital of Tugurejo there are primigravida petient are in the stage of labor when on the 1 active phase. Mother states can not stand the pain that is felt especially in the abdomen, waist, back, and spread to the backbone, so the mother continues to feel pain during the 1 stage of labor. The purpose of this study was to determine the effect of massage effleurage to reduction on the level of labor pain of stage I active phase in primigravida at Bougenville room of local General Hospital of Tugurejo Semarang. Methode: This research is a quasy experimental approach to one group pre test – post test design without control group. The study population was all primigravida mothers birth normally in local General Hospital of Tugurejo. The sampling technique by using Accidental Sampling. Samples are used 23 respondents. Instrument used is NRS observation sheet. Analysisstatistic used Wilcoxon test.Result : Pain level result obtained before doing Massage Effleurage the mean value of 3,78, after doing Massage Effleurage the mean value of 2,96 with p-value (0,000) ≤ α (0,05) and the value of z count : -4,359.Conclusion: There are any effect of massage effleurage to reduction on the level of labor pain of stage I active phase in primigravida at Bougenville room of local General Hospital of Tugurejo Semarang.